Pedagogia da rua: a educa????o sob o olhar do oprimido que mora na rua - Paula, Fernando Leonel Henrique Sim??es de (2016)
This dissertation analyzes the notion (or notions) of regular education as part of a set of other ideological instruments, structures the worldview of the social groups that have access to it. It examines more specifically the vision of the excluded, so-called "homeless". Speaking about the "homeless", this work refers to those the segments that are deprived of the most elementary rights and, therefore, suffer the most perverse forms of oppression and neglect in our Country. Based on Freire's view that the oppressed produce not only knowledge, but in specific situations, contribute with his knowledge to transform and overcome the status quo, this work develops the hypothesis that there is one or more) concept(s) about the regular education formulated by those oppressed segments that can contribute to the reflection about a broader sense of culture and civilization. It is a qualitative research. Eighteen interviews were developed by the researcher with the homeless population of the City of S??o Paulo, of both sexes, in three locations that are described in the research universe. In addition to this the researcher developed his personal observation from his own experience of also living more than three decades in the streets of the same city. From this material he extracted all the empirical material. The analysis of the representations of ???street population???, especially about school and regular education was the focus of the research.